Essays on consumer credit - Fantinatti, Amanda Miranda (2023)
Credit portability has been advocated as a significant instrument to promote competition in the banking industry. In 2014, the Brazilian Central Bank (BCB) introduced a regulatory framework to facilitate consumer credit portability. In Chapter 1, we explore the spatial local banking concentration in Brazil to investigate how this institutional change affected local credit markets. Our findings provide robust evidence that credit portability led to a reduction in interest rates and a surge in credit volume, mainly benefiting the categories of loans most affected by the legislative changes. In Chapter 2, using the Brazilian administrative credit registry data with the universe of all consumer loans originated by banks in the country from 2013 to 2019, we document high borrowing interest rates, which vary systematically with individual characteristics. In particular, even after controlling for several observable individual attributes – such as income, occupation, and default probabilities, low-income individuals pay higher interest rates than high-income borrowers. In Chapter 3, we quantitatively analyze a consumer credit market with these characteristics observed in Brazil in a model with endogenous default, where consumers face idiosyncratic income shocks. We perform counterfactual analyses to assess the impact of different financial reforms on borrowing rates, consumption inequality, consumption insurance, and welfare. We find that reforms aiming to reduce intermediation costs and bank market power have sizeable average and distributional welfare implications.